问题 解答题
请先阅读下列一段内容,然后解答问题:
因为:
1
1×2
=1-
1
2
1
2×3
=
1
2
-
1
3
1
3×4
=
1
3
-
1
4
,…,
1
9×10
=
1
9
-
1
10

所以:
1
1×2
+
1
2×3
+
1
3×4
+…+
1
9×10
=(1-
1
2
)+(
1
2
-
1
3
)+(
1
3
-
1
4
)+…+(
1
9
-
1
10
)
=1-
1
2
+
1
2
-
1
3
+
1
3
-
1
4
+…+
1
9
-
1
10
=1-
1
10
=
9
10

计算:
(1)
1
1×2
+
1
2×3
+
1
3×4
+…+
1
2007×2008

(2)
1
1×3
+
1
3×5
+
1
5×7
+…+
1
49×51
答案

(1)原式=1-

1
2
+
1
2
-
1
3
+…+
1
2007
-
1
2008
=1-
1
2008
=
2007
2008

(2)∵

1
1×3
=
1
3
=
1
2
(1-
1
3
),
1
3×5
=
1
15
=
1
2
×(
1
3
-
1
5
),…
1
49×51
=
1
2
×(
1
49
-
1
51
),

∴原式=

1
2
(1-
1
3
+
1
3
-
1
5
+…+
1
49
-
1
51
)=
1
2
(1-
1
51
)=
25
51

选择题
判断题